Process assessment of fencing coaches and referees within the scope of the covid-19 normalization steps - Yusuf Barsbuga (Ozlem Book Center, 2023)
The objective of this study is to measure and construe the opinions of the coaches and referees who are actively participating in fencing competitions in our country and who are licensed by the Turkish Fencing Federation (TFF) for the year of 2020, regarding the organizations to be planned and the issues to be paid attention, within the scope of the Covid-19 normalization steps. An online data collection form was used as a data collection tool in this study, which was structured through the qualitative research method. In the analysis process of the data obtained, the data analysis program called MAXQDA was used. While closed-ended questions were summarized by indicating percentages, the content analysis method was used in the process of analyzing open-ended question and answer reports. The data obtained were visualized with the help of frequency tables and code maps. Finally, some of the opinions of the participants, which were coded, were directly conveyed by interpreting the findings obtained through the tables and code maps.  It was determined as a result of the study that the Covid-19 pandemic that poses impacts on the entire world affects the attitudes of fencing coaches and referees to participate in organizations. In the activities planned to be organized, the sub-codes like attending without an audience, open-air competitions, provision of spaciousness and ventilation means in the selection of a competition hall, and risk approval notification are classified.